Na(+)-Stimulated Transport of l-Methionine in Brevibacterium linens CNRZ 918 - Ferchichi, Mohamed (1987)
The transport of l-methionine by the gram-positive species Brevibacterium linens CNRZ 918 is described. The one transport system (K(m) = 55 μM) found is constitutive for l-methionine, stereospecific, and pH and temperature dependent. Entry of l-methionine into cells is controlled by the internal methionine pool. Competition studies indicate that l-methionine and α-aminobutyric acid share a common carrier for their transport. Neither methionine derivatives substituted on the amino or carboxyl groups nor d-methionine was an inhibitor, whereas powerful inhibition was shown by l-cysteine, s-methyl-l-cysteine, dl-selenomethionine and dl-homocysteine. Sodium plays important and varied roles in l-methionine transport by B. linens CNRZ 918: (i) it stimulates transport without affecting the K(m), (ii) it increases the specific activity (on a biomass basis) of the l-methionine transport system when present with methionine in the medium, suggesting a coinduction mechanism. l-Methionine transport requires an exogenous energy source, which may be succinic, lactic, acetic, or pyruvic acid but not glucose or sucrose. The fact that l-methionine transport was stimulated by potassium arsenate and to a lesser extent by potassium fluoride suggests that high-energy phosphorylated intermediates are not involved in the process. Monensin eliminates stimulation by sodium. Gramicidin and carbonyl cyanide-m-chlorophenylhydrazone act in the presence or absence of Na(+). N-Ethylmaleimide, p-chloromercurobenzoate, valinomycin, sodium azide, and potassium cyanide have no or only a partial inhibitory effect. These results tend to indicate that the proton motive force reinforced by the Na(+) gradient is involved in the mechanism of energy coupling of l-methionine transport by B. linens CNRZ 918. Thus, this transport is partially similar to the well-described systems in gram-negative bacteria, except for the role of sodium, which is very effective in B. linens, a species adapted to the high sodium levels of its niche.